Innovation in Career Guidance Services For High School Students Through the Discovery Learning Model - Abdul Hadi; Edi Purwanta; Budi Astuti (Arus Jurnal Psikologi dan Pendidikan, 2026)
Career guidance is closely related to the career development of high school students in the educational environment. Career guidance services have obstacles, one of which is that the service approach has not been running optimally so that one approach model is needed, one of which is discovery learning. The purpose of this study is to examine insights into analyzing career guidance services for high school students through the Discovery Learning approach. The research method used in this study is a descriptive qualitative approach. This approach was chosen because it is to explore and analyze career guidance services for high school students through the Discovery Learning approach. Data sources used include accredited scientific journals and relevant research reports, especially those published in the last 5 years, to ensure the collected data is up-to-date and contextual. The analysis procedure was carried out by identifying the main themes that emerged in the literature related to career guidance services for high school students through the Discovery Learning approach. The results of the study show that the discovery learning approach in career guidance services can be developed through several steps or stages of service, which adapt the principles of discovery learning . The stages that are often used include: 1) Stimulus: 2) Problem identification, 3) Data / information collection 4) Processing and verification of information, 5) Generalization / reflection. In addition, the Discovery Learning approach increases students' active involvement in the career guidance service process, because students play an active role in finding information and constructing meaning for their own career understanding.